The Meta-Analysis of Coaching Learning Process Management - Tanatpornpong, Kankanit; Na Nakorn, Natchadarat (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI : 10.14456/pnuhuso.2023.8 The purpose of this research was to analyze the basic characteristics of research on coaching learning process management and to analyze the basic characteristics of the research that affect the effect size of research on coaching learning process management. Research papers on learning process management with coaching during the year 2012-2020 were analyzed. The research tools consisted of research data extraction form and research quality assessment form, data analysis statistic such as percentage, mean, standard deviation, effect size: d, t-test, F-test and multiple regression analysis. According to the document analysis, the quality of several research papers on coaching learning process management in public universities, Early Childhood Department was at a good level. The results of the analysis of variance on the effect size revealed that there were 12 variables research-characteristics that made the effect size different at the statistical significance level of 0.05, 7 variables for the initial characteristics of the research, 1 variable for the content of the research, 3 variables for the methodology of the research and 1 variable for research results. The results of the multiple regression analysis revealed that the 4 variables that affected the effect size were ordered from the greatest to the least, the field of research is early childhood, research field not specified, mixed research type and number of pages excluding appendices. The body of knowledge of the coaching learning process management can be organized in a variety of formats at all level of education while the coaching process, learning materials and the coaching period is adjusted according to the situation.